Forbidden: Receiving Pope Francis's Condemnation of Nuclear Weapons - Drew Christiansen, Carole Sargent (Georgetown University Press, 2023)
Moral theologians, defense analysts, conflict scholars, and nuclear experts imagine a world free from nuclear weapons At a 2017 Vatican conference, Pope Francis condemned nuclear weapons. This volume, issued after the 60th anniversary of the Cuban Missile Crisis, presents essays from moral theologians, defense analysts, conflict transformation scholars, and nuclear arms control experts, with testimonies from witnesses. It is a companion volume to A World Free from Nuclear Weapons: The Vatican Conference on Disarmament (Georgetown University Press, 2020). Chapters from the perspectives of missile personnel and the military chain of command, industrialists and legislators, and citizen activists show how we might achieve a nuclear-free world. Key to this transition is the important role of public education and the mobilization of lay movements to raise awareness and effect change. This essential collection prepares military professionals, policymakers, everyday citizens, and the pastoral workers who guide them, to make decisions that will lead us to disarmament.